Adenocarcinoma of Lung Presenting as Lambert-Eaton Myasthenic Syndrome - Sumera Bukhari MD; Rabia Soomro MD; Shaikh Fawwad MD; Chikezie Alvarez MD; Sara Wallach MD (SAGE Publishing, 2017)
Lambert-Eaton myasthenic syndrome (LEMS) is a paraneoplastic neuromuscular junction disorder. LEMS presents with muscular weakness and fatigability, mainly involving the proximal lower limbs. There are 2 types of LEMS depending on the etiology: paraneoplastic and idiopathic. The paraneoplastic form, which constitutes more than a half of the cases, is mostly associated with intrathoracic neoplasms. Most cases are seen in patients with small cell lung cancer; other subtypes of lung cancer are extremely rare. In this article, we report a case of LEMS as a rare association with adenocarcinoma of the lung.